Approaches to the Theory of Hardship in France, Germany, and England - Reza Bastani Namaghi; Mohommad Bagher Parsapoor (حقوق فناوریهای نوین, 2020)
The hardship of enforcing a contract is one of the most frequent problems in any legal system after a crisis; In this regard, the necessity of explaining a comprehensive theory about the hardship, especially in the pandemic of covid-19 as the most terrible crisis in recent centuries, is strongly felt. Today, many contemporary legal systems, including countries such as France, Germany, and England, have responded to the hardship of enforcing the contract with convergent approaches. These legal systems, while explaining the necessary condition of hardship, have also provided certain solutions for the problems of this matter in the realm of contract theory. The approaches of contemporary legal systems to the hardship can be categorized under the two general forms with the titles of "hardship as impossibility" and "maintaining the contract while reviewing it". Paying attention to these approaches in the Iranian legal system will provide very insightful achievements for Iranian jurists which can be used to achieve a proper balance between the principle of necessity and contractual justice.